Synthesis and Characterization of Zinc Vanadate Nanostructures for Supercapacitor Applications - Ramavathu, Lakshmana Naik; Tumma, Balanarsaiah (Trends in Sciences, 2022)
A simple hydrothermal approach was used to successfully produce nanostructured Zinc vanadate (Zn3V2O8), which was calcined at 450 ℃. The structural, optical and surface morphological features of calcined Zn3V2O8 nanoparticles were investigated using a variety of analytical techniques. The produced Zn3V2O8 nanoparticles had an orthorhombic crystalline structure, with an average crystallite size of 35.14 nm, according to the X-ray diffraction pattern (XRD). Transmission electron microscopy (TEM) analysis evaluated the spherical shaped Zn3V2O8 nanoparticles. The calcined catalyst was characterized by Fourier Transform-Infrared spectroscopy (FT-IR) analysis to analyse bonding interactions between the metal fragments within the composites. The nanoparticles obtained from hydrothermal synthesis were of size 37.2 nm, and the zeta-potential of nanoparticles was found to be −25.4 mV, indicating excellent dispersion and stability. The spectrophotometer was used to analyse the UV-Vis diffuse reflectance spectra (DRS). Cyclic voltammetry and electrochemical impedance spectroscopy were used to study the electrochemical behavior of Zn3V2O8 nanostructures. The specific capacitance value of the synthesized nanoparticles was 248.5 Fg−1. The active composite material was exploited as an electrode for the Supercapacitor application, and it revealed that synthesized Zn3V2O8 nanoparticles might lead to a possible application for future energy storage technologies. HIGHLIGHTS Zinc vanadate nanostructures have been prepared using easy and economical hydrothermal technique and are explored for supercapacitor application Electrochemical behaviour of zinc vanadate nanostructures were investigated by cyclic voltammetry, electrochemical impedance spectroscopic analysis and galvano static charge discharge analysis This zinc vanadate nanostructures exhibited a maximum specific capacitance of 248.5 F g−1 in the HCl electrolyte It clearly revealed that synthesized nanoparticles may lead to potential application for forthcoming energy storage devices GRAPHICAL ABSTRACT